The first social contract? Situating the prophetic pledge of allegiance within the trend of global constitutionalism - Nasir Hussan Wani; Areesha Azhar (UIN Kiai Haji Achmad Siddiq Jember, 2025)
Over the past decade, global constitutionalism has progressively sought to constrain the power of digital platforms. Nevertheless, existing frameworks largely rely on Western social contract traditions, often overlooking the structural inequities present in digitally mediated governance. This article argues that the prophetic pledge of allegiance (bai’ah) is fundamental covenantal form of the social contract, offering an alternative paradigm of political legitimacy distinct from liberal individualism. It utilises a qualitative, library-based methodology that integrates socio-historical reconstruction of early Islamic primary sources with normative-conceptual and comparative constitutional analysis. The article demonstrates that bai’ah produces four fundamental constitutional principles: mutual consent, normative constraints on authority, safeguarding of the public interest, and collective accountability. These findings indicate that legitimacy in the prophetic model is based not on superficial procedural adherence but on a morally binding and mutually accountable political relationship. This study reconstructs bai’ah as a foundation for constitutional ethics, thereby enriching current discussions on global and digital constitutionalism by providing a more diverse normative framework for reconsidering consent, accountability, and justice in platform governance. The covenantal logic of bai’ah offers a valuable framework for assessing and normatively limiting private digital power, especially when current governance structures inadequately safeguard vulnerable communities.